2018
DOI: 10.1002/etc.4225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrodynamic conditions and temperature on polar organic chemical integrative sampling rates

Abstract: The effects of changing hydrodynamic conditions and changing temperatures on polar organic chemical integrative sampler (POCIS) sampling rates (R ) were investigated for 12 crop protection chemicals. Exposure concentration was held constant in each laboratory experiment, and flow velocities were calculated from measured mass transfer coefficients of the water boundary layer near the surface of POCIS devices. At a given temperature R generally increased by a factor of 2 to 5 between a stagnant condition and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 41 publications
(80 reference statements)
2
18
0
1
Order By: Relevance
“…The values of R s at 1500 rpm were higher than those at 400 rpm. This tendency is consistent with the findings of several previous studies [5,11,12,[22][23][24][25][26]. In general, the mass transfer of chemicals from water to sorbent under low flow conditions is governed by the water boundary layer.…”
Section: Batch Sorption Experiments and Calculation Of R Ssupporting
confidence: 92%
See 1 more Smart Citation
“…The values of R s at 1500 rpm were higher than those at 400 rpm. This tendency is consistent with the findings of several previous studies [5,11,12,[22][23][24][25][26]. In general, the mass transfer of chemicals from water to sorbent under low flow conditions is governed by the water boundary layer.…”
Section: Batch Sorption Experiments and Calculation Of R Ssupporting
confidence: 92%
“…Conversely, the water turbulence prevalent under high flow conditions decreases the thickness of the water boundary layer. However, at some point, which is reported to be approximately 6 cm/s [25], an increase in turbulence no longer affects the sampling rate [23]. The flow velocities in the 1 L glass beaker under 400 rpm and 1500 rpm were calculated to be 1.0 cm/s and 18 cm/s, respectively ( Table 2).…”
Section: Batch Sorption Experiments and Calculation Of R Smentioning
confidence: 99%
“…A greater increase in sampling rates was observed between flow velocities V 0 to V 1 (Supplemental Data, Figure S3), because on average sampling rates increased by a factor of 3 between stagnant ( V 0 ) and flow condition V 1 . Djomte et al (2018) found that sampling rates increased by a factor of 2 to 5 between stagnant and flow conditions. For these same authors (Djomte et al 2018), pesticide sampling rates remained constant over the range of velocities from 6 to 21 cm/s.…”
Section: Resultsmentioning
confidence: 99%
“…Djomte et al (2018) found that sampling rates increased by a factor of 2 to 5 between stagnant and flow conditions. For these same authors (Djomte et al 2018), pesticide sampling rates remained constant over the range of velocities from 6 to 21 cm/s. We made the same observation: the sampling rates of pharmaceuticals slightly increased between flow velocities 2 to 3 and 6 to 7 cm/s and then again between 6 to 7 and 20 cm/s, by an average factor of 1.1 ± 0.4 and 1.4 ± 0.2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation